2016
DOI: 10.1007/s00253-016-8031-5
|View full text |Cite
|
Sign up to set email alerts
|

Penicillin V acylases from gram-negative bacteria degrade N-acylhomoserine lactones and attenuate virulence in Pseudomonas aeruginosa

Abstract: Virulence pathways in gram-negative pathogenic bacteria are regulated by quorum sensing mechanisms, through the production and sensing of N-acylhomoserine lactone (AHL) signal molecules. Enzymatic degradation of AHLs leading to attenuation of virulence (quorum quenching) could pave the way for the development of new antibacterials. Penicillin V acylases (PVAs) belong to the Ntn hydrolase superfamily, together with AHL acylases. PVAs are exploited widely in the pharmaceutical industry, but their role in the nat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
24
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(26 citation statements)
references
References 59 publications
1
24
1
Order By: Relevance
“…This gene was cloned into pGEX-4T-2 and expressed in E. coli DH5α demonstrating the AHL degradation activity of P6 strain. Although previous studies have reported that penicillin acylases are capable of degrading AHLs in other bacteria 57,58 , this activity had not previously been identified in the species Pseudomonas segetis. The actual physiological significance of AHL-degrading enzymes remains largely unclear 59 .…”
Section: Discussionmentioning
confidence: 83%
“…This gene was cloned into pGEX-4T-2 and expressed in E. coli DH5α demonstrating the AHL degradation activity of P6 strain. Although previous studies have reported that penicillin acylases are capable of degrading AHLs in other bacteria 57,58 , this activity had not previously been identified in the species Pseudomonas segetis. The actual physiological significance of AHL-degrading enzymes remains largely unclear 59 .…”
Section: Discussionmentioning
confidence: 83%
“…The sequence similarity within the Ntn-hydrolase family is very low and the enzymes within this family exhibit quaternary structures ranging from heterodimers (PGAs), homotetramers (PVAs) to the complex four homoheptameric rings forming the 20S proteasome (Unno et al, 2002; Mukherji et al, 2014; Sunder et al, 2016). However, a conservation of their tertiary fold structure is strongly pointing toward their evolutionary relationship (Hewitt et al, 2000).…”
Section: Quorum Quenching Acylasesmentioning
confidence: 99%
“…In addition, two tryptophan residues are thought to be important for the appropriate orientation of the substrate by providing a hydrophobic pocket for the acyl chain (PvdQ: Trpβ162 and Trpβ187; Pa PVA: Trp23 and Trp87). Ligand docking was performed in Discovery Studio 3.0 (Accelrys, United States) for PvdQ, and Glide’s extra precision for Pa PVA (Sunder et al, 2016). All structural figures were prepared in Pymol NRG studio.…”
Section: Quorum Quenching Acylasesmentioning
confidence: 99%
See 2 more Smart Citations